Exercise prevents fatal stress-induced myocardial injury in obese mice - Dun, Yaoshan; Hu, Zihang; You, Baiyang; Du, Yang; Zeng, Lingfang; Zhao, Yue; Liu, Yuan; Wu, Shaoping; Cui, Ni; Yang, Fan; Liu, Suixin (Frontiers in Endocrinology, 2023)
INTRODUCTION: This study aimed to explore whether aerobic exercise (AE) can prevent fatal stress-induced myocardial injury. METHODS: Thirty C57BL/6J mice were divided into either a normal diet, high-fat diet, or high-fat diet plus AE (n=10 per group). The AE protocol consisted of eight weeks of swimming. At the end of the diet and AE interventions, the mice were stimulated with fatal stress caused by exhaustive exercise (forced weight-loaded swimming until exhaustion), after which cardiac function was evaluated using echocardiography, myocardial ultrastructure was examined using transmission electron microscopy, and myocardial apoptosis was assessed using western blotting and TUNEL. Mitophagy, mitochondrial biogenesis and dynamics, and activation of the macrophage migration inhibitor factor (MIF)/AMP-activated protein kinase (AMPK) pathway were evaluated using quantitative PCR and western blotting. Obesity phenotypes were assessed once per week. RESULTS: AE reversed high-fat diet-induced obesity as evidenced by reductions in body weight and visceral fat compared to obese mice without AE. Obesity exacerbated fatal stress-induced myocardial damage, as demonstrated by impaired left ventricular ejection fraction and myocardial structure. The apoptotic rate was also elevated upon fatal stress, and AE ameliorated this damage. Obesity suppressed mitophagy, mitochondrial fission and fusion, and mitochondrial biogenesis, and these effects were accompanied by suppression of the MIF/AMPK pathway in the myocardium of mice subjected to fatal stress. AE alleviated or reversed these effects. CONCLUSION: This study provides evidence that AE ameliorated fatal stress-induced myocardial injury in obese mice. The cardioprotective effect of AE in obese mice might be attributed to improved mitochondrial quality.